Key imaging features for differentiating cystic biliary atresia from choledochal cyst: prenatal ultrasonography and postnatal ultrasonography and MRI - Shin, Hyun Joo (Ultrasonography, 2021)
PURPOSE: This study compared clinical and radiologic differences between cystic biliary atresia (cBA) and choledochal cyst (CC) type Ia/b. METHODS: Infants (≤12 months old) who were diagnosed with cBA or CC type Ia/b from 2005 to 2019 were retrospectively reviewed. Imaging features on preoperative ultrasonography (US) and magnetic resonance imaging (MRI) were compared between the cBA and CC groups. Logistic regression and area under the receiver operating characteristic curve (AUC) analyses were performed for the diagnosis of cBA. Changes in cyst size were also evaluated when prenatal US exams were available. RESULTS: Ten patients (5.5% of biliary atresia cases) with cBA (median age, 48 days) and 11 infants with CC type Ia/b (Ia:Ib=10:1; median age, 20 days) were included. Triangular cord thickness on US (cutoff, 4 mm) showed 100% sensitivity and 90.9% specificity (AUC, 0.964; 95% confidence interval [CI], 0.779 to 1.000) and cyst size on MRI (cutoff, 2.2 cm) had 70% sensitivity and 100% specificity (AUC, 0.900; 95% CI, 0.690 to 0.987) for diagnosing cBA. Gallbladder mucosal irregularity on US and an invisible distal common bile duct on MRI were only seen in the cBA group (10 of 10). Only the CC group showed prenatal cysts exceeding 1 cm with postnatal enlargement. CONCLUSION: Small cyst size (<1 cm) on prenatal US, triangular cord thickening (≥4 mm) and gallbladder mucosal irregularity on postnatal US, and small cyst size (≤2.2 cm) and an invisible distal common bile duct on MRI can discriminate cBA from CC type Ia/b in infancy.